Evaluation of the effectiveness of bedaquiline and delamanid treatment among children and adolescents with multi-drug-resistant pulmonary tuberculosis - M.I. Sakhelashvili; I.L. Platonova; O.I. Sakhelashvili-Bil; Z.I. Piskur (Сучасна педіатрія: Україна, 2023)
Introduction. Against the backdrop of multiple and widespread drug resistance of Mycobacterium tuberculosis (MDR-TB), there has been a significant decline in the effectiveness of treatment of tuberculosis (TB) patients in Ukraine and globally. Therefore, in recent years, new antimycobacterial drugs, such as bedaquiline (Bdq), delamanid (Dlm) and pretomanid, have been introduced to improve treatment efficacy in adults, children and adolescents.